Conceptual Innovative Arabic Language Lesson Plan Based on 21st Century Skills - Firza, Agus Ghulam (CV. Rayyan Dwi Bharata, 2025)
The learning implementation design or called RPP is an important component in manifesting the form of teaching and learning activities. The design of the implementation of integral learning is the design of the implementation of learning that involves different processes to get good results. This requires special attention that the design of the implementation of learning has a very large effect on teacher performance and the quality of students. Plus the phenomenon that is increasingly happening in the 21st century is the absolute need for students to have qualified skills that become an important standard in the life of globalization. This is something that the teacher must respond to quickly in his expertise in creating the concept of an innovative Arabic language learning implementation design that is oriented towards 21st century skills. However, the problem is that it is difficult for teachers to formulate learning objectives, develop unique 21st century learning steps including strategies, models, methods and their development in the field due to lack of education about understanding the process of preparing innovative 21st century skills-based RPP with an insufficient period of time. Thus the challenges of teachers will be even greater, new innovations will continue to be generated. On that basis, this study aims to understand and know more clearly the conceptual design of the implementation of innovative Arabic learning based on 21st century skills. This study uses a qualitative method with the type of library research (library research), which is to obtain correct and good information on research criteria from all reading and recording activities. in the form of books, journals, articles, survey results, seminar materials and other research results.